2000
DOI: 10.1080/08880010050120881
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinoma in a 9-Year-Old Boy

Abstract: Gastric carcinoma is an extremely rare cancer in children. A case is presented of a 9-year-old boy admitted to The University Hospital Brno with a 4-month history of abdominal pain, anorexia, weight loss, nausea, and vomiting. Several of his family members died from or have been treated for cancer. Barium meal examination performed 2 months prior to admission was nondiagnostic. When gastroendoscopy, laparoscopy, and abdominal computer tomography scan were performed, the diagnosis of adenocarcinoma of the stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…Our patient is a new case of de-novo occurrence such as those that have been sporadically reported in the first and second decades of the life [1,6,9]. The lack of any kind of causative information and the normal histological findings of gastric mucosa outside the tumor suggest that our case was a new primary gastric carcinoma, which may be classified as de-novo occurrence, and which ended fatally 4 months after diagnosis in spite of complete resection and administered chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Our patient is a new case of de-novo occurrence such as those that have been sporadically reported in the first and second decades of the life [1,6,9]. The lack of any kind of causative information and the normal histological findings of gastric mucosa outside the tumor suggest that our case was a new primary gastric carcinoma, which may be classified as de-novo occurrence, and which ended fatally 4 months after diagnosis in spite of complete resection and administered chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Reports of childhood gastric carcinomas are limited to case reports [35][36][37]. Larger cohorts include younger adults (age b40) [38].…”
Section: Discussionmentioning
confidence: 96%
“…4,5 Children suffering from gastric cancer often present with abdominal pain, distension, anorexia, emesis/hematemesis, melena, hematochezia, and/or an abdominal mass. [6][7][8][9] Unfortunately, early diagnosis is extremely rare, and the onset of symptoms is frequently indicative of advanced disease and a poor prognosis. 10 After studying 127 patients younger than age 35 years, Windham et al 11 concluded that early diagnosis conferred no survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Children with symptoms of peptic ulcer disease, an abdominal mass, or prolonged hematemesis should have an early upper GI endoscopy with biopsy to avoid a possible delay in diagnosis. 7 Although ultrasound scan and CT studies often are used to aid in diagnosis and surgical strategy, they are nondiagnostic and can be falsely negative. 7 Because of its infrequency in children, treatment strategies, including surgery, chemotherapy, and radiotherapy, are largely based on principles used in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation